Photosynthetic induction in Eucalyptus urograndis seedlings and cuttings measured by an open photoacoustic cell - Barja, P. R.; Mansanares, A. M.; Da Silva, E. C.; Magalhaes, ACN; Alves, PLCA (Acad Sci Czech Republic, Inst Experimental Botany, 2001)
Photosynthetic induction in leaves of four-month-old Eucalyptus urograndis seedlings and of cuttings obtained from adult trees that were previously dark-adapted was studied by the in vivo and in situ Open Photoacoustic Cell Technique, Results for the gas exchange component of the photoacoustic (PA) signal were interpreted considering that the gas uptake component would have a phase angle nearly opposite to that of the oxygen evolution component. By subtracting the thermal component from the total PA signal, we studied the competition between gas uptake and oxygen evolution during the photosynthetic induction. Seedlings presented a net oxygen evolution prior to cuttings, but cuttings reached a higher steady-state photosynthetic activity. The chlorophyll (Chl) a/b ratio and the Chl fluorescence induction characteristic F-v/F-m were significantly higher for cuttings, while there was no difference between samples in stomata density and leaf thickness. Thus the differences in PA signals of seedlings and cuttings are associated to differences between the photosystem 2 antenna systems of these samples.
Keywords: chlorophyll fluorescence; clone differences; gas uptake; leaf thickness; oxygen evolution; photobaric signal; photothermal signal; stomata density